Understanding everyday life and mental health recovery through CHIME. Issue 5 (13th November 2017) - Piat, Myra; Seida, Kimberly; Sabetti, Judith
Abstract : Purpose: The purpose of this paper is to understand how daily life reflects the recovery journeys of individuals with serious mental illness (SMI) living independently in the community. Design/methodology/approach: The go-along technique, which blends participant observation and interviewing, was used to gather data from 19 individuals with SMI living in supported housing. Data were analyzed through the CHIME framework of personal recovery, which includes social connectedness, hope and optimism, identity, meaning in life, and empowerment. Findings: Applying the CHIME framework to qualitative data reveals the multiple ways in which everyday experiences, within and beyond formal mental healthcare environments, shapes personal recovery processes. Research limitations/implications: Combining novel methods and conceptual frameworks to lived experiences sharpens extant knowledge of the active and non-linear aspects to personal recovery. The role of the researcher must be critically considered when using go-along methods. Practical implications: Practitioners working with this population should account for the role of socially supportive and financially accessible spaces and activities that support the daily work of recovery beyond the context of formal care and services. Originality/value: This study utilizes an innovative method to illustrate the crucial role of daily and seemingly banal experiences in fostering or hindering personal recovery processes. It is also the one of the first studies to comprehensively apply the CHIME framework to qualitative data in order to understand the recovery journeys of individuals with SMI living in supported housing.